Timor-Leste Poverty Assessment : Poverty in a New Nation - Analysis for Action, Volume 2. Technical Report - World Bank (Washington DC, 2013)
Timor-Leste has achieved enormous progress in rehabilitating its economy, reconstructing its infrastructure, reintegrating its refugees and building the key elements of a sustainable political process in an environment of internal peace. It now faces many challenges of nation-building and of overcoming the deprivation affecting the lives of the poor. This report written in two volumes lays out the challenge of poverty reduction in Timor-Leste. It is based on the first nationally-representative household survey collected during August to December 2001. The report's objectives are modest: to set a baseline for the new country on the extent, nature and dimensions of poverty; and to assist the decision making of the newly elected government and its efforts in formulating, implementing and monitoring its Poverty Reduction Strategy. The overall objective was not to lay out the elements of poverty strategy but rather to present evidence on the basis of which the Timorese can define and refine their own poverty reduction strategy. The key challenge lies now in formulating a poverty monitoring plan that includes both quantitative and participatory elements, and lays out the institutional arrangement for data analysis and reporting to ensure that the collected data inform policy making and program design.